Atomically Dispersed Dual‐Site Cathode with a Record High Sulfur Mass Loading for High‐Performance Room‐Temperature Sodium–Sulfur Batteries. Issue 1 (29th November 2022) - Zhang, Bin‐Wei; Cao, Liuyue; Tang, Cheng; Tan, Chunhui; Cheng, Ningyan; Lai, Wei‐Hong; Wang, Yun‐Xiao; Cheng, Zhen‐Xiang; Dong, Juncai; Kong, Yuan; Dou, Shi‐Xue; Zhao, Shenlong
Abstract: Room‐temperature sodium–sulfur (RT‐Na/S) batteries possess high potential for grid‐scale stationary energy storage due to their low cost and high energy density. However, the issues arising from the low S mass loading and poor cycling stability caused by the shuttle effect of polysulfides seriously limit their operating capacity and cycling capability. Herein, sulfur‐doped graphene frameworks supporting atomically dispersed 2H‐MoS2 and Mo1 (S@MoS2 ‐Mo1 /SGF) with a record high sulfur mass loading of 80.9 wt.% are synthesized as an integrated dual active sites cathode for RT‐Na/S batteries. Impressively, the as‐prepared S@MoS2 ‐Mo1 /SGF display unprecedented cyclic stability with a high initial capacity of 1017 mAh g −1 at 0.1 A g −1 and a low‐capacity fading rate of 0.05% per cycle over 1000 cycles. Experimental and computational results including X‐ray absorption spectroscopy, in situ synchrotron X‐ray diffraction and density‐functional theory calculations reveal that atomic‐level Mo in this integrated dual‐active‐site forms a delocalized electron system, which could improve the reactivity of sulfur and reaction reversibility of S and Na, greatly alleviating the shuttle effect. The findings not only provide an effective strategy to fabricate high‐performance dual‐site cathodes, but also deepen the understanding of their enhancement mechanisms at an atomic level. Abstract : An integrated dual‐active‐site cathode is developed by wreathing monolayered MoS2 and Mo1 on sulfur‐doped graphene frameworks for high‐performance room‐temperature sodium–sulfur batteries. The constructed atomic level MoS2 ‐Mo1 with delocalized electron effects facilitates substantial charge transfer and a completely reversible reaction between S and Na, thus alleviating the shuttle effect.